Community structure of a propanil-degrading consortium and the metabolic pathway of Microbacterium sp. strain T4-7. (November 2015) - Hou, Ying; Li, Shuhuan; Dong, Weiliang; Yuan, Yi; Wang, Yicheng; Shen, Wenjing; Li, Jingquan; Cui, Zhongli
Abstract: A propanil-degrading consortium T4 was enriched from propanil polluted soil using propanil as the sole carbon and energy source. The community structure of consortium T4 was analyzed using restriction fragment length polymorphism (RFLP). Strain T4-7 isolated from consortium T4 was identified as a Microbacterium sp. based on physiological, biochemical characteristics and 16S rRNA gene analysis. Strain T4-7 was capable of transforming 98.94% of 100 mg L −1 propanil to a stable product within 10 h; the metabolite was identified as 3, 4-dichloroaniline (DCA) by GC–MS. Strain T4-7 most likely converted propanil via cleavage of the amide bond to DCA and propionate and could utilize propionate as its sole carbon source for growth, but could not further degrade DCA. The propanil hydrolase from the crude enzyme preparation from strain T4-7 showed an optimal reaction temperature of 45 °C and pH of 7.0, with broad stability from 4 to 30 °C and pH 6.0–10.0. Moreover, strain T4-7 was capable of transforming 2-chlor- N -(2-ethyl-6-methylbenzene) acetamide (CMEPA, the intermetabolite of acetochlor) to 2, 6-methyethyaniline (MEA) based on GC–MS. The enzymatic properties for CMEPA degradation were consistent with propanil. The results suggested that propanil and CMEPA may be hydrolyzed by the same amidase. Highlights: A highly effective propanil-degrading consortium T4 was domesticated. Community structure of T4 was analyzed with RFLP; the dominant bacteria mostly belonged to uncultured bacteria. Strain T4-7 was the first reported Microbacterium sp. to degrade acetanilide herbicides. Metabolites during propanil and CMEPA degradation were identified as DCA and MEA, respectively. Enzymatic properties of strain T4-7 acting on propanil and CMEPA was studied for the first time.